The impacts of land reclamation on the accumulation of key elements in wetland ecosystems in the Sanjiang Plain, northeast China. (June 2018) - Gao, Chuanyu; Zhang, Shaoqing; Liu, Hanxiang; Cong, Jinxin; Li, Yunhui; Wang, Guoping
Abstract: The Sanjiang Plain, which is located in northeastern China, given the distribution of temperate freshwater wetlands there and this region has considerable significance in ensuring food security in China. Two periods of farmland reclamation that occurred during the last 100 years led to the loss of nearly 80% of the area of the native wetlands, and the development of agriculture has also increased the potential environmental risks to the residual wetlands. To evaluate the effects of farmland reclamation on the accumulation of key elements within the residual wetland ecosystems, six wetland profiles in the Sanjiang Plain are selected in this study. Using age-depth models and the concentrations of key elements, the historical accumulation rates (ARs) of carbon (C), nutrient elements (N and P) and potentially toxic elements (Hg, As, Pb, Cu, and Zn) over the last 150 years are reconstructed. The results show that the ARs of the potentially toxic elements in two of the wetland profiles begin to increase during the first reclamation period (AD 1900–1930). The ARs of both of the key elements clearly increase in all of the wetland profiles during the second reclamation period (AD 1950–1980). After land reclamation had ceased, increases in population and the development of industry became major factors that caused the potential environmental risks to wetlands to continue to increase from AD 1980 to the present. During the last 100 years, reclamation has increased the potential environmental risks and has led to the storage of additional carbon in the residual wetlands of the Sanjiang Plain. Highlights: The impacts of historical reclamation on wetlands in the Sanjiang Plain are evaluated. Element accumulation rates (ARs) are clearly affected by reclamation. Potentially toxic element ARs began to increase during the first reclamation period. All key element ARs clearly increased during the second reclamation period. Reclamation led to the storage of additional carbon in the surrounding wetlands.